Set-theoretic type solutions of the braid equation - (:unkn) unknown (Elsevier BV, 2024)
In this paper we begin the study of set-theoretic type solution of the braid equation. Our theory includes set-theoretical solutions as basic examples. More precisely, the linear solution associated to a set-theoretic solution on a set X can be regarded ...
Keywords: Álgebra; Teoría de conjuntos